2007
DOI: 10.1124/dmd.107.019299
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparative Studies of Zebrafish and Human Recombinant Dihydrofolate Reductases—Inhibition by Folic Acid and Polyphenols

Abstract: ABSTRACT:Dihydrofolate reductase (DHFR) catalyzes folic acid reduction and recycles dihydrofolate generated during dTMP biosynthesis to tetrahydrofolate. DHFR is the main target of methotrexate, the most widely used agent for antifolate therapy. Nevertheless, the emergence of methotrexate-resistance has greatly impeded the curative potential of this drug. Therefore, drugs with improved efficacy are still in demand, as well as an efficient in vitro assay system and animal model for antifolate drug discovery. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
(34 reference statements)
0
33
0
Order By: Relevance
“…Embryos were staged according to Kimmel et al (1995). Total RNA isolation and cDNA library construction from zebrafish embryos and tissues were prepared with RNAzol B reagent (Tel-Test Inc., Friendswood, TX) and the SMART-RACE cDNA Amplification Kit (Clontech) as described previously (Kao et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryos were staged according to Kimmel et al (1995). Total RNA isolation and cDNA library construction from zebrafish embryos and tissues were prepared with RNAzol B reagent (Tel-Test Inc., Friendswood, TX) and the SMART-RACE cDNA Amplification Kit (Clontech) as described previously (Kao et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Well established tools of molecular biology for gene manipulation have also significantly assisted progress with zebrafish. We have started an extensive study of folate-mediated one-carbon metabolism in zebrafish (Chang et al, 2006(Chang et al, , 2007Kao et al, 2008). In this study, we cloned the coding sequence of zebrafish ␥GH (z␥GH) from a zebrafish cDNA library and developed an efficient protocol for expression and purification of the recombinant z␥GH.…”
mentioning
confidence: 99%
“…These results suggested that EGCG could act as an antifolate compound in the same way as MTX and TMP. Since these first reports describing the inhibition of DHFR by tea polyphenols, several studies by us and other laboratories have reported that EGCG inhibits DHFR from a variety of biological sources (Navarro-Martínez et al, 2005;NavarroPerán et al, 2007;Hannewald et al, 2008;Kao et al, 2008;Spina et al, 2008;Sánchez-del-Campo et al, 2010a). Recently, a screening of DHFR-binding drugs by MALDI-TOFMS demonstrated that EGCG is an active inhibitor of DHFR and has a relative affinity between that of pyrimethamine and MTX (Hannewald et al, 2008).…”
Section: The Antifolate Activity Of Tea Catechinsmentioning
confidence: 99%
“…John Scott's group has studied this pharmacology (Sweeney et al, 2009) and reported no detectable serum FA after doses of 100 or 200 μg FA were ingested for 14 weeks, however, FA was measurable at the highest level (400 μg) tested (Sweeney et al, 2007). The review by Smith discusses potential metabolic interference (Kao et al, 2008) and toxicity (Smith et al, 2008) of the provitamin FA some of which is noted in Figure 25. for PSAV > 2 ng/ml/yr.…”
Section: Demethylating Agents: Reversal Of Aberrant Methylation In Thmentioning
confidence: 99%
“…Modulation of One-Carbon Metabolism by B Vitamins: Implications for Transformation and Progression of Prostate Cancer 209 1) FA may directly inhibit DHFR (Kao et al, 2008) 2) FA competes with H2FA for reduction 3) 10-CO-FA inhibits DHFR 4) FA induces 10-CO-FA (D'Urso- Scott et al, 1974;Pratt & Cooper, 1971)? 5) PSMA of prostate cell membrane enhances folate monoglutamate of microenvironment 6) Possible transient production of toxic diopterin and teropterin and other polyglutamates by action of FPGS on FA (Hoffbrand et al, 1976;Shane, 2010) 7) PSM' splice variant FPH produces folate monoglutamates intracellularly 8) B2 modulates MTHFR (Bates & Fuller, 1986;Matthews & Baugh, 1980;Matthews & Haywood, 1979;McNulty et al, 2002) 9) DHFA SAM (Matthews & Daubner, 1982), and FA-(slightly) (Matthews & Haywood, 1979) inhibit MTHFR 10) CH3-THF trapped by B12 deficiency 11)Testosterone increases DHFR activity Rovinetti et al, 1972) 12) Estrogen increases FPH activity.…”
Section: Wwwintechopencommentioning
confidence: 99%